PENGARUH KOMPENSASI FINANSIAL DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI PADA PT. ASURANSI SINARMAS CABANG DENPASAR - Nurtika, Herland; Sariyathi, Ni Ketut (E-Jurnal Manajemen, 2018)
The purpose of this study was to analyze the effect of financial compensation and job satisfaction on organizational commitment. The population in this study were 49 employees. Sample determination method used is saturated sample method, then the entire population will be sampled. Object in this research is financial compensation and job satisfaction and its influence to organizational commitment in PT. Asuransi Sinarmas Denpasar Branch. Data collection methods used were questionnaires and interviews. Data analysis technique used is multiple linear regression. The result of this research is financial compensation have positive and significant effect to organizational commitment, and job satisfaction have positive and significant influence to organizational commitment. Keyword : financial compensation, job satisfaction, organizational commitment